Detritus, trophic dynamics and biodiversity - John C. Moore; Eric L. Berlow; David C. Coleman; Peter C. de Ruiter; Quan Dong; Alan Hastings; Nancy Collins Johnson; Kevin S. McCann; Kim Melville; Peter J. Morin; Knute Nadelhoffer; Amy D. Rosemond; et al. (Ecology Letters, 2004)
Traditional approaches to the study of food webs emphasize the transfer of local primary productivity in the form of living plant organic matter across trophic levels. However, dead organic matter, or detritus, a common feature of most ecosystems plays a frequently overlooked role as a dynamic heterogeneous resource and habitat for many species. We develop an integrative framework for understanding the impact of detritus that emphasizes the ontogeny and heterogeneity of detritus and the various ways that explicit inclusion of detrital dynamics alters generalizations about the structure and functioning of food webs. Through its influences on food web composition and dynamics, detritus often increases system stability and persistence, having substantial effects on trophic structure and biodiversity. Inclusion of detrital heterogeneity in models of food web dynamics is an essential new direction for ecological research.